Integrative transcriptomic and metabolomic data provide insights into gene networks associated with lignification in postharvest Lei bamboo shoots under low temperature. (30th January 2022) - Hou, Dan; Lu, Haiwen; Zhao, Zhongyu; Pei, Jialong; Yang, Huqing; Wu, Aimin; Yu, Xuejun; Lin, Xinchun
Highlights: Transcriptomic and metabolic analysis of lignification in LT-treated bamboo shoots. LT induced strong accumulations of JA and lignin biosynthesis precursors. JA and lignin biosynthesis genes form network modules with LT responsive factors. Two pathways of LT-lignification and LT-JA-lignification identified. Abstract: Lei bamboo ( Phyllostachys violascens ) shoots are delicious food in Asia. Here, the molecular basis of lignification in postharvest Lei bamboo shoots under low temperature (LT) is revealed by transcriptomic and metabolomics analyses for the first time. We identified substantial accumulations of jasmonates (JAs) and major lignin biosynthesis precursors (coumarin, trans-4-coumaric acid, trans-ferulic acid and L-phenylalanine). Transcriptome analysis indicated that some regulatory genes were significantly differentially expressed, and the expression patterns of them were highly consistent with the changes in the key lignin precursors or JA profiles. Co-expression analysis showed that the LT responsive genes PvCRPK-4/-5, PvICE2-1/2, PvDREB2B might form a network module with the lignin ( PvC3H-2/3, PvC4H-2/4, PvCAD-1/2/3/4, etc . ) or JA biosynthesis genes ( PvOPR2, PvJAZ-4 and PvPEX5, etc . ), indicating a LT-lignification or LT-JA-lignification regulatory pathway in Lei bamboo shoots. Above all, our findings provide new an insight into the LT-associated lignification in postharvest bamboo shoots.